ISSUES OF IMPROVING THE INSTITUTION OF AUTHORIZED ECONOMIC OPERATOR IN THE REPUBLIC OF UZBEKISTAN - I. D. Toraxodjayeva (Modern American Journals, 2025)
The country is taking systemic measures to improve customs administration and increase the efficiency of the state customs service of the Republic of Uzbekistan, as well as to further simplify customs procedures. In particular, the institution of authorized economic operators has been introduced, which grants the right to use simplified customs procedures to participants in fair foreign economic activity that meet the requirements established by international standards in the field of customs administration. This article examines the specifics of the functioning and legal regulation of the institution of an authorized economic operator in customs control to further simplify customs procedures, increase the eficiency of customs authorities, as well as eliminate bureaucratic barriers to business development and improve the investment climate in the country. The experience of developed countries in the practice of using the institution of authorized economic operators has been studied and the existing problems and ways of solving them in the Republic of Uzbekistan have been analyzed.
Keywords: Kyoto Convention, Framework Standards, World Customs Organization, Authorized Economic Operator, Special Simplifications, Customs Administration.